Role of Oral Tranexamic Acid in Reducing Peroperative and Postoperative Hemorrhage in External Dcr Surgery - Aktar, Nasima; Hasan, Faridul; Rahman, Anisur; Shuchi, Tarzeen Khadiza; Nasrin, Mossammat Shoheli (Journal of Dhaka Medical College, 2023)
Background: External dacryocystorhinostomy (DCR) is now a well-established, effective approach to relieve nasolacrimal duct obstruction. Per operative hemorrhage obscure the operative field during surgery.so it is difficult to carry on an uncomplicated surgery. Moreover postoperative hemorrhage has become an added problem. The objective of this study is, to evaluate the effect of oral tranexamic acid in reducing both per operative and postoperative hemorrhage in external DCR surgery. Methods: This hospital based interventional quasi experiment included 60 patients with chronic dacryocystitis at DMCH between January 2014 to June 2014.Oral formulation of tranexamic acid 500mg two capsule and tablet Vit B complex as placebo started 1 hour prior to DCR surgery and continued up to second postoperative day in intervention and control group respectively. In every case, the rate of hemorrhage was evaluated peroperatively and postoperatively. Findings: In this study, mean duration of operation was 35.98 (range 30 to 51) min in group-A and 54.13(45-75min) minutes in group-B. Perioperative mean blood loss was of 15.03 ml with a maximum blood loss of 25ml in group A and was 33.57ml with maximum blood loss of 39ml in group B. Mean postoperative bleeding was 2.55ml with maximum blood loss 5ml In group A and was 5.53ml with maximum blood loss 13ml in group B. postoperatively no bleeding was found in 24(73.33%) cases in group A and 10(40%) cases in group B. Conclusion: This study suggests that oral tranaxemic acid significantly reduces peroperative and postoperative hemorrhage and reduces duration of surgery and improves the quality of DCR surgery. J Dhaka Med Coll. 2021; 30(2) : 196-201